Constitutional rights, formal principles and balance - Gavião Filho, Anizio Pires (Revista de Direitos e Garantias Fundamentais, 2023)
This research aims to address the role of formal principles in the balancing of principles. The central question to be examined is whether formal principles can be balanced against material principles. A straightforward balancing with material principles or a mixed balancing leads to subconstitutionalization. The answer lies in the epistemic model of the balancing. Formal principles require respect for the legislator’s decisions made in the space of epistemic discretion. The result is that formal principles serve to determine the limits of the intensity of the jurisdiction’s control over the decisions of the democratically legitimated legislature. Research developed under the comparative bibliographical method.